The Influence of Gamification on English Vocabulary Retention in Online Learning Platforms - Ummi Qalsum Arif (Yayasan Pendidikan Bima Berilmu, 2025)
The rapid advancement of digital learning technologies has transformed language acquisition, with gamification emerging as an innovative strategy to enhance vocabulary retention. This study aims to examine the impact of gamification on English vocabulary acquisition in online learning platforms by analyzing its effects on vocabulary retention, learner engagement, motivation, and cognitive load. Drawing on theoretical frameworks such as Self-Determination Theory, Cognitive Load Theory, and Engagement Theory, the study also discusses the challenges and limitations of applying gamified methods in vocabulary learning. Gamification elements, including points, rewards, leaderboards, and interactive challenges, have been shown to improve learner motivation, engagement, and retention by creating an immersive and stimulating learning environment. Empirical studies indicate that gamified learning enhances cognitive processing, reduces cognitive overload, and promotes sustained participation. However, challenges such as cognitive distractions, reliance on extrinsic motivation, and variations in learner preferences must be addressed to optimize the effectiveness of gamification. This study highlights the potential of gamified approaches in modern language education while emphasizing the need for well-designed instructional strategies to maximize learning outcomes. Future research should further examine the long-term effects of gamification on vocabulary retention and explore inclusive approaches that cater to diverse learner needs.